Petung Bamboo As Microwave Absorber At 8-12 Ghz Frequency - Adam Aswin Usman (Peneliti.net, 2022)
It has been successful in characterizing activated carbon from petung bamboo using the carbonization method as a microwave absorber in the frequency range of 8-12 GHz. The micro-order activated carbon material, which is 23.5 µm, is a semiconductor with an electrical conductivity value of 2.16 x 10-7 S/m. The activated carbon of petung bamboo was carbonized at a temperature of 600 oC and an activated carbon phase was formed at an angle of 2θ 22,93o and 42.98o and the results of the FTIR characterization showed the presence of a C=C bond at wave number 1535.39 cm-1 as confirmation of the formation of activated carbon. The VNA test showed that the optimum reflection loss on the activated carbon sample of petung bamboo with a thickness of 1 mm was -21.2 dB at a frequency of 10.8 GHz